Efficacy of 3 days/wk resistance training on myofiber hypertrophy and myogenic mechanisms in young vs. older adults - Kosek, David J; Kim, Jeong-su; Petrella, John K; Cross, James M; Bamman, Marcas M (Journal of applied physiology (1985), 2006)
Departments of 1 Physiology and Biophysics and 3 Surgery, University of Alabama at Birmingham, and 2 Geriatric Research, Education, and Clinical Center, Veterans Affairs Medical Center, Birmingham, Alabama Submitted 22 November 2005 ; accepted in final form 4 April 2006 Resistance training (RT) has shown the most promise in reducing/reversing effects of sarcopenia, although the optimum regime specific for older adults remains unclear. We hypothesized myofiber hypertrophy resulting from frequent (3 days/wk, 16 wk) RT would be impaired in older (O; 6075 yr; 12 women, 13 men), sarcopenic adults compared with young (Y; 2035 yr; 11 women, 13 men) due to slowed repair/regeneration processes. Myofiber-type distribution and cross-sectional area (CSA) were determined at 0 and 16 wk. Transcript and protein levels of myogenic regulatory factors (MRFs) were assessed as markers of regeneration at 0 and 24 h postexercise, and after 16 wk. Only Y increased type I CSA 18% ( P < 0.001). O showed smaller type IIa (16%) and type IIx (24%) myofibers before training ( P < 0.05), with differences most notable in women. Both age groups increased type IIa (O, 16%; Y, 25%) and mean type II (O, 23%; Y, 32%) size ( P < 0.05). Growth was generally most favorable in young men. Percent change scores on fiber size revealed an age x gender interaction for type I fibers ( P < 0.05) as growth among Y (25%) exceeded that of O (4%) men. Myogenin and myogenic differentiation factor D (MyoD) mRNAs increased ( P < 0.05) in Y and O, whereas myogenic factor (myf)-5 mRNA increased in Y only ( P < 0.05). Myf-6 protein increased ( P < 0.05) in both Y and O. The results generally support our hypothesis as 3 days/wk training led to more robust hypertrophy in Y vs. O, particularly among men. However, this differential hypertrophy adaptation was not explained by age variation in MRF expression. sarcopenia; myogenin; MyoD; myosin heavy chain Address for reprint requests and other correspondence: M. M. Bamman, UAB Dept. of Physiology and Biophysics, Muscle Research Laboratory, GRECC/11G VA Medical Center, 1530 3rd Ave., South Birmingham, AL 35294-0001 (e-mail mbammanatuab.edu )